Overdraw prevention and imaginary shooting line practice in archery - Aslan, E.; Yoncalik, O. (Journal of Physical Education, Recreation & Dance, 2023)
Learning a new skill involves learning the appropriate basic form. In archery basic form is shooting form and it has globally accepted standards. Shooting form general lines are divided into phases as stance, nocking the arrow, hooking, and gripping, setup, drawing, loading, anchoring, holding, expansion and aiming, release and follow-through. Archery skills are characterized by repeating the same movements with high similarity and consists of phases that continue one after another. This article is about simple and affordable teaching tips for archery teaching. It proposes an answer to the question "How can I get correct shooting form more easily?".